2004
DOI: 10.1089/152308604771978381
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidative Stress and Impaired Thioredoxin Expression in Spontaneously Hypertensive Rats

Abstract: As oxidative stress plays a crucial role in the development and pathogenesis of hypertension, we analyzed the redox (reduction/oxidation) status in tissues from Wistar-Kyoto rats (WKY), spontaneously hypertensive rats (SHR), and stroke-prone SHR (SHRSP). Expressions of 8-hydroxy-2'-deoxyguanosine, a marker for oxidative stress-induced DNA damage, and protein carbonylation, a marker for oxidation status of proteins, were enhanced in aorta, heart, and kidney from SHR and SHRSP compared with WKY. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 40 publications
5
87
1
6
Order By: Relevance
“…The TRX/GRX enzyme systems are especially important in protecting against ischemia/reperfusion injury after myocardial infarction, atherosclerotic plaque rupture, left ventricular hypertrophy in congestive heart failure, and kidney oxidative stress. In SHRs and SHRSP rats, TRX levels were lower in kidneys by both immunohistochemistry/Western blots and real time PCR, when compared with those in normal WKY rats (319). Of note, whereas the roles of TRX/GRX systems are better understood in the cardiovascular disease, their role in the kidney is just emerging.…”
Section: Nistala Et Al 2054mentioning
confidence: 93%
“…The TRX/GRX enzyme systems are especially important in protecting against ischemia/reperfusion injury after myocardial infarction, atherosclerotic plaque rupture, left ventricular hypertrophy in congestive heart failure, and kidney oxidative stress. In SHRs and SHRSP rats, TRX levels were lower in kidneys by both immunohistochemistry/Western blots and real time PCR, when compared with those in normal WKY rats (319). Of note, whereas the roles of TRX/GRX systems are better understood in the cardiovascular disease, their role in the kidney is just emerging.…”
Section: Nistala Et Al 2054mentioning
confidence: 93%
“…The effects of ROS are mediated through redoxsensitive regulation of multiple signaling molecules and second messengers. [5][6][7] Several studies have demonstrated excessive amounts of ROS in essential hypertensive patients and various animal models of hypertension; [8][9][10][11][12] these patients and experimental animals have a diminished antioxidant status, 13 which contributes to the accumulating evidence that increased vascular oxidative stress could be involved in the pathogenesis of essential hypertension. 2,3,14 Recently, a strong association between blood pressure and some oxidative stress-related parameters was demonstrated.…”
Section: Vascular Oxidative Stress and Hypertensionmentioning
confidence: 99%
“…78,79 Recent studies have demonstrated the importance of the thioredoxin system in the maintenance of a reduced redox state and in the pathophysiology of hypertension. 80 It has been reported that Oxidative stress in hypertension R Rodrigo et al impaired thioredoxin expression in spontaneously hypertensive rats 81 and in endothelial cells negatively regulates ROS production in VSMC through thioredoxin upregulation. 82 Thus, thioredoxin could be an important therapeutic target for the prevention and treatment of oxidative stress and hypertension.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…Although very little is known about the relationship between TRX and Ang II, there is evidence that the TRX system is modulated by the renin angiotensin system, since ACE inhibition improves severity of myocarditis via redox regulation mechanisms involving TRX. In addition, in SHR, a model of Ang II-dependent hypertension, vascular TRX expression is impaired (60).…”
Section: Processes Whereby Ros Influence Signaling Moleculesmentioning
confidence: 99%